Thermal Transmittance (U-value) Evaluation of Innovative Window Technologies (Future Cities and Environment, 2020)
Calculation of heat transfer in windows has a direct impact on the thermal transmittance on highly insulated glazing components. A series of experimental tests were carried out in order to calculate the U-value of active insulated windows using the Heat Flux Meter method (ISO 9869-1); this to compare the insulation properties of traditional single glass, double glazing with different aerogel fillings and vacuum glazing windows. The use of this heat flux method utilised an environmental chamber to provide a temperature difference of 15 °C reporting the U-values as follows: traditional double glazing 3.09 W/m2·K, vacuum glazing 1.12 W/m2·K, and double glazing with aerogel pillars 2.52 W/m2·K. On the other hand, double glazing with KGM wheat starch reported 3.40 W/m2·K, double glazing with granulated aerogel 2.07 W/m2·K and heat insulation solar glass 1.84 W/m2·K. Vacuum glazing recorded optimal results under these experimental conditions, describing a U-value 78 % lower when compared to traditional single glazing window units (5.15 W/m2·K). Installation of windows with lower thermal transmittance are expected to increase in the global market to meet the current construction codes, aimed for achieving net zero carbon buildings.